PEMANFAATAN KITOSAN SEBAGAI BAHAN DASAR BIOPLASTIK RAMAH LINGKUNGAN - Pardi Pardi; Herawati Herawati; Siti Adila; Atdril Atdril (Universitas Ubudiyah Indonesia, 2026)
PEMANFAATAN KITOSAN SEBAGAI BAHAN DASAR BIOPLASTIK RAMAH LINGKUNGAN